Στρατηγική περιβαλλοντική μελέτη: ενεργειακό κέντρο Βασιλικού - Παναγή, Γιώργος (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The trigger for the implementation of this study was the imperative need to preserve the environment and the incorporation of laws that now serve as helpers for the protection efforts. Ιn this context, the Strategic Environmental Impact Study (SEPA) is an indispensable tool to demonstrate the environmental impacts of plans and programs and is considered to be crucial to optimizing decision-making that is consistent with the requirements for sustainable development. The following tool is used to evaluate the Vasilikos Energy Center, which is a strategic project of Cyprus, mainly because of the purposes that it is intended to serve. Initially, the existing strategic environmental study elaborated for the Vasilikos Energy Center, is presented comprehensively as well as the present state of the project and the local environment. The current postgraduate dissertation concerns the evaluation of the implementation of the strategic environmental study in the Vasilikos Energy Center. After studying the significance of the strategic environmental study and the energy center and then after considering the relevant legislation, we made an effort to identify the weaknesses and propose measures to improve the environment of the area. In particular, it is assessed whether the existing strategic environmental study for the Vasilikos Energy Center is based on and meets the requirements of the legislation and prioritizes the effective protection of the environment from anthropogenic activities and the impacts resulting from the operations of the energy Center. In addition, this specific project aims to examine the conditions and prospects for diversification, upgrading and proposed measures to improve both the strategic environmental study and the local environment. The methodology followed for the implementation of this postgraduate study is both the bibliographic review and the implementation of criteria for the evaluation of the strategic environmental study concerning the energy center of Vasilikos.
Keywords: Strategic Environmental Study; Energy Center; Vasilikos; Στρατηγική περιβαλλοντική μελέτη; Ενεργειακό Κέντρο; Βασιλικό